Leadership style and higher education performance: A bibliometric analysis of research trends and evolution - Triany, Novika Ayu; Akbar, Muhammad; Sonni, Alem Febri (Edelweiss Applied Science and Technology, 2026)
This study aims to map the development of research on leadership styles and higher education performance through a bibliometric analysis of scientific publications indexed in Scopus. The dataset comprised 2,872 articles published between 2019 and 2024. Bibliometric methods were employed to identify publication trends, patterns of scholarly collaboration, dominant themes, and the conceptual evolution shaping the relationship between leadership style and institutional performance in higher education. The findings indicate that leadership studies in higher education are no longer confined to leadership typologies but have expanded into broader dimensions, including organizational dynamics, human resource management, institutional culture, and organizational communication. The principal finding confirms that communication constitutes a central element of leadership practice, as it plays a vital role in articulating institutional vision, fostering a conducive working culture, and aligning actions across academic and administrative units. In addition, leadership effectiveness is influenced by external factors, including government policy and institutional context. This study concludes that communication serves as a strategic mechanism linking leadership to the improvement of higher education performance. The implications of this study highlight the importance of strengthening leaders’ communication competence as a foundation for developing adaptive and sustainable governance in higher education institutions.